Utilization of Palm Shell Ash as a Filler in Making AC-WC Type Porous Asphalt - Anggreana, Vella; Alwiyah, Sy. Sarah; Sari, Junita (Universitas Negeri Padang, 2024)
The background to the research that will be carried out is that the large amount of standing water on the road pavement in each rainy season results in disturbances to motorists' comfort. This is due to impermeable road pavement and poor drainage along the road. Porous asphalt can increase rainwater absorption, thereby reducing puddles on the road surface. Porous asphalt is a new breakthrough in the world of road pavement to reduce the appearance of puddles of water when it rains. Porous asphalt is also designed to have high porosity so that water can flow through side channels and a waterproof base layer to prevent water from seeping into the subbase layer and road body so as to minimize puddles of water on the road surface which often occur after rain and disrupt the smooth flow of traffic. cross. Advances in road pavement technology have encouraged researchers to conduct research using palm shell ash (fly ash) as a filler in porous asphalt mixtures. The use of palm shell ash is expected to increase the stability value and have large cavities so that water can pass through the road surface, as well as to reduce palm oil waste in Indonesia. The objectives of this research are 1. To find out the optimum asphalt content value in porous asphalt mixtures, 2. To know the results of using palm shell ash at 0%, 1% and 2% as a filler for porous asphalt mixtures in flexible road pavement. The research method is Marshall and Permeability Testing. The tests that will be carried out on a laboratory scale use an AC-WC hot mix asphalt system with guidance, namely the basics of asphalt concrete road construction. The research results showed that by adding palm shell ash as a filler in making AC-WC type porous asphalt, it showed that the stability value was higher, while the permeability value was lower, meaning that the addition of palm shell ash to the porous asphalt mixture did not have a significant effect because it was smaller. air voids in the mixture. The addition of palm shell ash to the porous asphalt mixture increases the stability value which can increase the ability of road construction to accept loads, but the pavement layer is not permeable and water flows over the surface more slowly.